2017
DOI: 10.1038/s41598-017-08553-2
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the thermoelectric effect by mechanical manipulation of the electron’s quantum phase in atomic junctions

Abstract: The thermoelectric voltage developed across an atomic metal junction (i.e., a nanostructure in which one or a few atoms connect two metal electrodes) in response to a temperature difference between the electrodes, results from the quantum interference of electrons that pass through the junction multiple times after being scattered by the surrounding defects. Here we report successfully tuning this quantum interference and thus controlling the magnitude and sign of the thermoelectric voltage by applying a mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The asymmetric feature in the thermocouple temperature can be explained by Landauer theory, which predicts a difference in the heat dissipation Δ Q at current upstream ( Q up ) and downstream ( Q down ) of a ballistic system as Δ Q = ( Q up − Q down ) ~ 2 GTSV b , where T and S are the temperature and the Seebeck coefficient, respectively 15 , 22 . On the other hand, while Au nanocontacts are reported to possess structure-dependent bi-thermoelectric properties 23 25 , previous studies reported negative thermopower of S Au = −4 μV/K as an average over many configurations measured 24 . Accordingly, Δ Q < 0 from the sign of S Au , and hence Q down > Q up , that explains the higher Δ T t observed under positive V b .…”
Section: Resultsmentioning
confidence: 96%
“…The asymmetric feature in the thermocouple temperature can be explained by Landauer theory, which predicts a difference in the heat dissipation Δ Q at current upstream ( Q up ) and downstream ( Q down ) of a ballistic system as Δ Q = ( Q up − Q down ) ~ 2 GTSV b , where T and S are the temperature and the Seebeck coefficient, respectively 15 , 22 . On the other hand, while Au nanocontacts are reported to possess structure-dependent bi-thermoelectric properties 23 25 , previous studies reported negative thermopower of S Au = −4 μV/K as an average over many configurations measured 24 . Accordingly, Δ Q < 0 from the sign of S Au , and hence Q down > Q up , that explains the higher Δ T t observed under positive V b .…”
Section: Resultsmentioning
confidence: 96%
“…Figure 3 shows the conductance change upon rupture of the junction. The conductance trace shows a step at 1 G 0 (2e 2 /h), corresponding to the Au atomic junction [24][25][26]. In the case of the Au atomic junction, a single channel of Au 6s contributes to electron transport, and the transmission of the channel is 100%.…”
Section: Resultsmentioning
confidence: 99%
“… 27 ) The sign of the thermopower of a material depends on the type of carrier (hole or electron). 28 ) If the carriers are holes, the HOMO stays close to the Fermi level of the single molecular junction. Meanwhile, the I - V curve measurement fixes the energy difference between the Fermi level and the conduction orbital, although it does not indicate whether the conduction orbital is below or above the Fermi level.…”
Section: Characterization Techniques For Single Molecular Junctionsmentioning
confidence: 97%
“…Similar mechanical switches have been reported using bipyridine, BDT, C 60 , Sc 3 N@C 80 , oligothiophene and Au atomic junctions. 28 , 30 , 40 )…”
Section: Innovation Of New Functionalitiesmentioning
confidence: 99%